Evaluation, management and outcome of upper urinary tract transitional cell carcinoma – A five year single center experience - Sandeep Puvvada (Asian Journal of Medical Sciences, 2016)
Aims and Objectives: To review a single centre experience in the evaluation, management and outcome of upper tract transitional cell carcinoma.